Estimating Macrofracture Toughness of Sandstone Based on Nanoindentation - Zilong Zhou; Boxiang Lei; Xin Cai; Yichao Rui (Geofluids)
An upscaling method for estimating macrofracture toughness by nanoindentation results was proposed in this study. Grid nanoindentation tests were conducted on sandstone samples to obtain micromechanical properties of indents, including elastic modulus, hardness, and stiffness. Multifactor cluster analysis was then carried out to categorize the sandstone into five mechanical phases. Finally, the macrofracture toughness was predicted by using the macroelastic modulus of the sample and the critical energy release rate of the weakest phase. To verify this method, the upscaling result was compared with the macrofracture toughness measured by the notched semicircular bending (NSCB) test. The discrepancy in the macrofracture toughness from our method and the NSCB test was 8.8%, which was acceptable. Also, it is proved that our method can provide more accurate upscaling results compared to other methods.